The Kansas squat test: A valid and practical measure of anaerobic power for track and field power athletes - Luebbers, P. E.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2015)
The Kansas squat test (KST) is a repetitive lifting test designed to measure relatively similar indices of lower-body power as the Wingate anaerobic test (WAnT). The purposes of this study were twofold: determine concurrent validity of the KST using the WAnT as the criterion measure and also demonstrate the KST as a practical test of anaerobic power for track and field athletes. Twenty-three track and field athletes participated (mean ± SD; 77.2 ± 16.8 kg, 175.6 ± 8.7 cm). Each completed the KST, and on a separate occasion, the WAnT for comparison. Correlation coefficients indicated significant relationships between the KST and the WAnT on measures of maximum test power (r = 0.920, p < 0.01) and mean test power (r = 0.929, p < 0.01), but not for relative fatigue (r = 0.030, p > 0.05). The posttest lactate response also lacked a significant relationship (r = -0.062, p > 0.05). These relationships were also present when athletes were examined in subgroups based on gender and event. Paired-samples t-tests indicated that while peak power and mean power were significantly higher for the KST (p = 0.01), relative fatigue and lactate were both significantly higher for the WAnT (p = 0.01). These significant differences were similar in the subsequent subgroupings of the athletes. These data support that the KST is a concurrently valid assessment of lower-body anaerobic power. This study further illustrates a practical lower-body power testing method that is lift specific, which may aid in improving training specificity for track and field power athletes.